(3Ydhe GdCQV hGdHjFI ddghGIs - (3ThGgjf, NjQ SdjeGfs ((3YeGf, GdCQOf (B:s (3OGQ GdeSjQI ddfTQ hGdJhRjY hGdWHGYI,s, 2005)
(3GdeGA hGdJQHI(B.s
(3jTJed Ydi EQLGYGJ HHdjhLQGajI(B.s
(3HHdjhLQGajI (B: (3U(B. 345.s
(3GdSfGfj(B.s
1.
Keywords: (3Ydhe GdCQVs; (3Yde GdHjFIs; (3GdLjhdhLjGs